UIFP Econometric models of Nigerian economy: some initials results - Olayide S.O; Olofin,S.O.; Iyaniwura J.O.; Adeniyi J.O. (Ibadan university of Ibadan, 1981)
This research paper contains findings by the university of Ibadan forecasting programme that examined the Nigeria economy market using the keynesian macro-model.
Includes index.
asm; 06/03/19
Arch
Keywords: Economic forecasting; Econometric models